A motorized vehicle-mounted sprayer as a new tool for chagas disease vector control - Carbajal de la Fuente, Ana Laura (2017)
Residual insecticide spraying still is the main tool used to suppress house infestations with Chagas disease vectors. While manual compression sprayers (MCS) have traditionally been used in Latin America, Mendoza’s vector control program from Argentina introduced the use of a modified motorized vehicle-mounted sprayer (VMS) with apparent advantages over MCS. We conducted a randomized intervention trial to evaluate the effectiveness and selected components of the performance of MCS and VMS. We assessed house infestation by Triatoma infestans in 76 previously-infested houses at 0, 1, 4 and 12 months postintervention. Infestations were reduced substantially, with no significant differences between treatments. End-point infestations were restricted to peridomiciles. Although VMS required less time to complete the house spraying than MCS, both treatments had similar performance and did not suppress infestations completely. The main relative advantages of VMS were a reduced physical effort, especially under harsh field conditions, and potential gains in spray coverage per unit of time.